Isokinetic strength of collegiate baseball pitchers during a season - Wilkin, L. D.; Haddock, B. L. (The Journal of Strength and Conditioning Research, 2006)
Pitching is suggested to expose the arm to physical stress that may lead to a decrease in strength. The purpose of this study was to examine the isokinetic internal and external rotational shoulder strength of Division II pitchers preseason, midseason, and postseason. The 9 pitchers were 23 +/- 0.67 years of age and weighed 91.2 +/- 3.14 kg. Each subject was evaluated utilizing a Biodex Isokinetic Dynamometer. Isokinetic internal and external concentric strength was assessed at 90° of shoulder abduction and 90° of elbow flexion at 300 and 450°/s at each time point. A repeated-measures analysis of variance statistical analysis was performed using SPSS software. All data are reported as mean +/- SEM. Mean internal peak torques at 300 and 450°/s preseason, midseason, and postseason were 50.66 +/- 2.27, 49.70 +/- 2.54, and 51.70 +/- 2.94 Nm and 37.14 +/- 2.54, 37.36 +/- 2.74, and 38.26 +/- 2.50 Nm, respectively. Mean external peak torques at 300 and 450°/s preseason, mid-season, and postseason were 30.16 +/- 1.69, 29.50 +/- 2.22, and 29.79 +/- 2.08 Nm and 17.68 +/- 2.15, 16.89 +/- 2.46, and 18.20 +/- 2.35 Nm, respectively. There were no differences in isokinetic internal or external concentric shoulder rotational mean peak torque of Division II pitchers at any speed tested or time point examined.